2008
DOI: 10.1002/rcm.3366
|View full text |Cite
|
Sign up to set email alerts
|

A fragmentation study of two compounds related to 4′‐demethylepipodophyllotoxin in negative ion electrospray ionization by MSn ion‐trap time‐of‐flight mass spectrometry

Abstract: High-resolution electrospray ionization multistage tandem mass spectrometry (MS 1-7) in negative ion mode was used to determine the accurate masses and fragmentation pathways of two compounds, 4'-demethylepipodophyllotoxin and 4'-demethyl-4-azido-4-deoxyepipodophyllotoxin, which are key intermediate compounds for the preparation of podophyllotoxin-type anti-cancer drugs. The deprotonated molecules [M-H]* of both compounds were readily observed in the conventional single-stage mass spectra due to the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…The [M À H] À ion of compound 8 at m/z 417 yielded a fragment ion at m/z 225 which resulted again from the cleavage of the ester bond while ring A cleaved as a neutral molecule. 20,21 Along with the loss of the CH 3 radical, a product ion at m/z 296 was also observed due to the loss of C 5 H 11 from the m/z 367 peak. Another product ion at m/z 209, corresponding to [M À H À C 11 H 12 O 4 ] À , was observed which further decarboxylated and yielded a fragment ion at m/z 165.…”
Section: Fragmentation Pattern Of Secondary Metabolites Of Lichensmentioning
confidence: 99%
See 1 more Smart Citation
“…The [M À H] À ion of compound 8 at m/z 417 yielded a fragment ion at m/z 225 which resulted again from the cleavage of the ester bond while ring A cleaved as a neutral molecule. 20,21 Along with the loss of the CH 3 radical, a product ion at m/z 296 was also observed due to the loss of C 5 H 11 from the m/z 367 peak. Another product ion at m/z 209, corresponding to [M À H À C 11 H 12 O 4 ] À , was observed which further decarboxylated and yielded a fragment ion at m/z 165.…”
Section: Fragmentation Pattern Of Secondary Metabolites Of Lichensmentioning
confidence: 99%
“…APCI-MS/MS spectra of ethyl haematomate (4) have been reported, however no fragmentation patterns were given. 20,21 The CID-MS/MS spectra and proposed mechanistic fragmentation pathway of sekikaic acid (8) are shown in Fig. 4.…”
Section: Fragmentation Pattern Of Secondary Metabolites Of Lichensmentioning
confidence: 99%
“…Many articles tended to the positions at C (15) or C(7) [18,19]. In this paper, the position C(7) was proposed so that the fragments could lose its C(16)-methoxyl moiety to form a double bond between C(15) and C (16) positions and after that ketone -enol tautomerism occurred to form a carbonyl at C(15) position. In MS 2 analysis, the [M þ H -AcOH -MeOH -CO] þ (1d) ion from aconitine (1) was obtained that could demonstrate the above-mentioned conjecture.…”
Section: Esi-it-tof Ms N Fragmentationsmentioning
confidence: 97%
“…The high intensity ions 1b, 1d, 2b, 3b, 3c, and 4d were all come from the loss of C(8) or C(16)-moiety. The discussions indicated that C(8) was the most active position and the activity of C(16) is slightly inferior in MS n experiments, the eliminations of moieties at C(8) and C (16) positions were the originations to generate base peak ions.…”
Section: Esi-it-tof Ms N Fragmentationsmentioning
confidence: 99%
See 1 more Smart Citation